2017
DOI: 10.1038/cddis.2017.455
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone mediates pancreatic cancer progression by glucocorticoid receptor, TGFβ and JNK/AP-1

Abstract: Glucocorticoids such as dexamethasone are widely co-prescribed with cytotoxic therapy because of their proapoptotic effects in lymphoid cancer, reduction of inflammation and edema and additional benefits. Concerns about glucocorticoid-induced therapy resistance, enhanced metastasis and reduced survival of patients are largely not considered. We analyzed dexamethasone-induced tumor progression in three established and one primary human pancreatic ductal adenocarcinoma (PDA) cell lines and in PDA tissue from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 54 publications
(69 reference statements)
3
47
2
Order By: Relevance
“…DEX supplementation led to a slow downregulation of TGFB1 expression in static cell cultures or in follicular thyroid cancer cells grown for four hours on the RPM ( Figure S2C). This observation could be cell-type specific, as DEX increased TGFB1 expression in prostate cancer and pancreatic ductal carcinoma cells [76,77]. TGF-β signaling is identified as one of the most altered pathways in ovarian tumor spheroids [78] and cell aggregation proved to be induced by TGF-β in ovarian cancer cells [79].…”
Section: Cell Detachment In Microgravity and Epithelial-mesenchymal Tmentioning
confidence: 92%
“…DEX supplementation led to a slow downregulation of TGFB1 expression in static cell cultures or in follicular thyroid cancer cells grown for four hours on the RPM ( Figure S2C). This observation could be cell-type specific, as DEX increased TGFB1 expression in prostate cancer and pancreatic ductal carcinoma cells [76,77]. TGF-β signaling is identified as one of the most altered pathways in ovarian tumor spheroids [78] and cell aggregation proved to be induced by TGF-β in ovarian cancer cells [79].…”
Section: Cell Detachment In Microgravity and Epithelial-mesenchymal Tmentioning
confidence: 92%
“…However, for epithelial tumors such as PDA, accumulating evidence indicates that GCs have anti-apoptotic effects and induce cancer progression and therapy resistance ( 5 , 6 ). In 2003, we reported the first in vivo evidence of induction of chemotherapy resistance due to pharmacological doses of DEX in a lung and cervical cancer cell line ( 7 ), and these data have been confirmed by several experimental studies ( 4 - 6 , 8 ). Additionally, clinical studies have indicated an increased likelihood of drug resistance, disease progression and metastasis in patients with glioblastoma, oral squamous cell carcinoma and cancers of the ovary, breast, prostate or lung due to GCs ( 8 - 15 ).…”
Section: Introductionmentioning
confidence: 76%
“…The present study is based on our recent finding that DEX meditates PDA progression through its actions on the GC receptor, TGF-β and JNK/AP1 ( 4 ) Here, we evaluate the mechanism underlying DEX-induced upregulation of TGF-β. Because a number of studies have suggested that miRNAs are important mediators of GC signaling ( 35 , 36 ), we performed miRNA microarray analysis and identified several significantly DEX-deregulated miRNAs, with miR-132 as the top down-regulated candidate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations